2004
DOI: 10.1523/jneurosci.5292-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of False Matches for Binocular Correspondence in Macaque Visual Cortical Area V4

Abstract: A plane lying in depth is vividly perceived by viewing a random-dot stereogram (RDS) with a slight binocular disparity. Perception of a plane-in-depth is lost by reversing the contrast of dots seen by one of the eyes to generate an anticorrelated RDS. From a computational perspective, the visual system cannot find a globally consistent solution for matching the left and right eye images of an anticorrelated RDS. The neural representation of a global match should therefore be insensitive to binocular disparity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 44 publications
(66 reference statements)
10
100
0
Order By: Relevance
“…We estimated the response latency of each neuron by Poisson spike train analysis (Legéndy and Salcman, 1985;Hanes et al, 1995;Tanabe et al, 2004). One neuron in the amygdala was excluded because its response latency could not be determined.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the response latency of each neuron by Poisson spike train analysis (Legéndy and Salcman, 1985;Hanes et al, 1995;Tanabe et al, 2004). One neuron in the amygdala was excluded because its response latency could not be determined.…”
Section: Methodsmentioning
confidence: 99%
“…This phosphor has the shortest decay time among the three phosphors in CRT displays, so turning off the other phosphors minimized interocular cross talk. For dichoptic presentation with a liquid crystal polarizing filter, interocular cross talk from the left eye to the right eye was 10%, whereas there was no measurable cross talk from the right eye to the left eye (Tanabe et al, 2004). We did not detect any interocular cross talk in dichoptic presentation with ferroelectric liquid crystal shutters.…”
Section: Visual Stimulimentioning
confidence: 95%
“…This is three times the latency of the visual response, or the latency of disparity selectivity (Uka et al, 2005). The increase in the delay of the choicepredictive activity from V4 to IT (230 ms) is disproportionate to the increase in the delay of the visual response or the disparity selectivity (ϳ20 ms) (Watanabe et al, 2002;Tanabe et al, 2004;Uka et al, 2005). Attention modulates neuronal activity in V4 and IT with a similar time course (Mehta et al, 2000).…”
Section: Latency Of Choice-predictive Activity During Fine Disparity mentioning
confidence: 99%
“…Early neurophysiological recordings revealed selectivity for binocular disparity at multiple levels of the visual hierarchy: V1 (Barlow et al 1967;Poggio and Fischer 1977), V2 (Thomas et al 2002;von der Heydt et al 2000), V3 (Adams and Zeki 2001;Felleman and Van Essen 1987;Poggio et al 1988), V4 (Hegde and Van Essen 2005;Connor 2002, 2005;Tanabe et al 2004;Watanabe et al 2002), MT/V5 (DeAngelis and Newsome 1999; Krug et al 2004;Palanca and DeAngelis 2003;DeAngelis 2004, 2006), MST (Eifuku and Wurtz 1999;Takemura et al 2002), IT (Janssen et al 2000(Janssen et al , 2001(Janssen et al , 2003Liu et al 2004;Tanaka et al 2001;Uka et al 2000Uka et al , 2005, and in regions of the parietal (caudal intraparietal sulcus) cortex (Taira et al 2000;Tsutsui et al 2002). Complementary evidence from human brain imaging implicated several areas across the visual, object-related, motion-related, and parietal cortex in the processing of disparity information (for reviews see Neri 2005;Orban et al 2006a,b).…”
Section: Disparity Processing and 3d Shape Perceptionmentioning
confidence: 99%
“…Neurophysiological evidence suggests that primary visual cortex does not respond to global constraints on correspondence Parker 1997, 2000), whereas this computation appears partially solved in V4 (Tanabe et al 2004) and predominantly so in IT (Janssen et al 2003). Selectivity for disparity-defined gradients is evident in MT/V5 (Nguyenkim and DeAngelis 2003), IT (Liu et al 2004), and CIP (Tsutsui et al 2002) and responses to shapes defined by curvature are found in IT (Janssen et al 2000(Janssen et al , 2001.…”
Section: Disparity Processing and 3d Shape Perceptionmentioning
confidence: 99%